Disruptions in RNA Splicing: A Key Regulator of Cognitive Impairment in Perioperative Neurocognitive Disorders - Xu-An Wang; Qing-Ya Wu; Xiao-Yu Shi; Xiao-Peng Wang; Yan-Yan Gao; Wei-Wei Zhang; Yi-Sheng Lu; Dan Liu; Ling-Qiang Zhu; Hua Zheng (Neuroscience Bulletin, 2026)
Perioperative neurocognitive disorders (PND) encompass a spectrum of cognitive impairments that emerge during the perioperative period. The pathogenesis of PND is multifactorial, involving complex interactions between neuroinflammation, impairment of synaptic plasticity, dysregulation of brain-derived neurotrophic factor (BDNF) signaling, oxidative stress, and mitochondrial dysfunction. RNA splicing is increasingly recognized as a critical player in nervous system function and dysfunction. In this review, we explore the role of RNA splicing in modulating the major pathogenic mechanisms of PND. We highlight how aberrant splicing events promote neuroinflammation by altering the expression of pro-inflammatory genes, disrupt synaptic plasticity by modifying the profiles of synaptic proteins and neurotransmitter receptors, and impair the expression and function of BDNF. Additionally, RNA splicing abnormalities exacerbate oxidative stress and mitochondrial dysfunction, further amplifying neuronal damage. By elucidating the intricate interactions between RNA splicing and these core pathological processes, this review reveals the close association between RNA splicing dysregulation and the molecular underpinnings of PND, and highlights its potential regulatory role in PND pathogenesis.